2022
DOI: 10.1158/1538-7445.sabcs21-p3-12-08
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P3-12-08: Neighborhood disadvantage predicts worse breast cancer-specific survival

Abstract: BackgroundAlthough advances in screening, detection, diagnosis, and treatment have reduced overall breast cancer mortality, well-documented socioeconomic and racial/ethnic disparities persist. The objective of this study was to utilize the area deprivation index (ADI), a compositive measure of neighborhood disadvantage, on breast cancer survival in South Florida, predominantly consisting of Miami-Dade County residents. The ADI is based on a measure created by the Health Resources & Services Administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Prior studies have identified that neighborhood disadvantage is associated with later stage at presentation, triple negative BC, and shorter survival in women with BC 4,8,30,31 . Disadvantaged neighborhoods are associated with marginalized populations, as economic and residential segregation has roots in structural racism 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have identified that neighborhood disadvantage is associated with later stage at presentation, triple negative BC, and shorter survival in women with BC 4,8,30,31 . Disadvantaged neighborhoods are associated with marginalized populations, as economic and residential segregation has roots in structural racism 32 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, most studies linking neighborhood disadvantage to shorter BC survival attribute this association to disparities in access to care 3–6 . However, recent studies have identified that disparities in BC survival remain between women living in disadvantaged compared with advantaged neighborhoods, even after controlling for multilevel access to care barriers, individual-level factors, tumor characteristics, and receipt of National Cancer Center Network guideline-concordant treatment 7,8 . This suggests unaccounted mechanisms that contribute to persistent BC survival disparities by neighborhood disadvantage.…”
mentioning
confidence: 99%
“…This residual association of neighborhood disadvantage with survival suggests that there are underlying mechanisms by which neighborhood disadvantage impacts survival that have not been accounted for. 7,8 Many of these studies are limited to specific geographic areas, limiting the generalizability of the study on a national level, or have limitations based on population choice, such as older Medicare patients with fee-for-service coverage, so results may not be generalizable to younger patients or those with other types of insurance. 9,10 Thus, a critical knowledge gap remains regarding whether breast cancer-specific survival disparities persist after accounting for individual, tumor, and treatment characteristics in a national, population-based cohort.…”
Section: Introductionmentioning
confidence: 99%
“…4 Prevailing evidence suggests that disparities in cancer treatment and mortality associated with individuals' race and ethnicity are not fully accounted for by individual-level, clinical, and demographic factors and that neighborhood factors influencing health and health care access could be contributors. [5][6][7][8] There has been growing interest in how area-level measures of socioeconomic status and environment are associated with health outcomes. Area-level measures have been associated with frailty, obesity, and cardiovascular disease as well as access to preventive health care in historically marginalized populations.…”
Section: Introductionmentioning
confidence: 99%
“…Area-level measures have been associated with frailty, obesity, and cardiovascular disease as well as access to preventive health care in historically marginalized populations. [4][5][6]9,10 In regard to cancer-specific outcomes, a higher Social Vulnerability Index (SVI) 11 score has been associated with patients being less likely to receive neoadjuvant chemotherapy or to use high-volume centers for surgical resection and with patients being more likely to encounter fragmented postoperative care. 7,8,11,12 Additionally, area-level factors have been associated with morbidity after controlling for sociodemographic factors among individuals with colorectal and breast cancer.…”
Section: Introductionmentioning
confidence: 99%